1992
DOI: 10.1007/bf02919405
|View full text |Cite
|
Sign up to set email alerts
|

Continuous culture of neuronal cells from adult human olfactory epithelium

Abstract: Cells from the olfactory epithelium of adult human cadavers have been propagated in primary culture and subsequently cloned. These cells exhibit neuronal properties including: neuron-specific enolase, olfactory marker protein, neurofilaments, and growth-associated protein 43. Simultaneously, the cells exhibit nonneuronal properties such as glial fibrillary acidic protein and keratin, the latter suggesting properties of neuroblasts or stem cells. These clonal cultures contain 5-10% of cells sufficiently differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 27 publications
7
62
0
Order By: Relevance
“…23), suggests that its absence could also influence the closely related to central nervous system neurons. They express neuron-specific enolase and make direct synaptic contacts with the central nervous system (24 …”
Section: Discussionmentioning
confidence: 99%
“…23), suggests that its absence could also influence the closely related to central nervous system neurons. They express neuron-specific enolase and make direct synaptic contacts with the central nervous system (24 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly to its rodent counterpart, olfactory neurogenesis is thought to occur in the adult human and it has been shown that post mortem olfactory tissue retains the capacity for neurogenesis and neuronal differentiation until at least 72 years of age (Wolozin et al, 1992;Feron et al, 1998;Murrell et al, 1996). In humans the olfactory mucosa covers a much smaller area when compared to other mammalian species, probably because of the fact that olfaction is less developed in humans than in other mammals (see Fig.…”
Section: What Is Known About the Human Olfactory System?mentioning
confidence: 96%
“…Olfactory neuroblasts (Wolozin et al, 1992b) and neurospheres (Roisen et al, 2001;Murrell et al, 2005) can be grown from the human olfactory mucosa. In the present study, olfactory neurospheres were generated from olfactory mucosa biopsies by growing the dissociated cells in serum-free medium containing EGF and FGF2.…”
Section: Technical Considerationsmentioning
confidence: 99%